Research on the Undulatory Motion Mechanism of Seahorse Based on Dynamic Mesh - Xinyu Quan; Ximing Zhao; Shijie Zhang; Jie Zhou; Nan Yu; Xuyan Hou (Applied Bionics and Biomechanics)
The seahorse relies on the undulatory motion of the dorsal fin to generate thrust, which makes it possess quite high maneuverability and efficiency, and due to its low volume of the dorsal fin, it is conducive to the study of miniaturization of the driving mechanism. This paper carried out a study on the undulatory motion mechanism of the seahorse’s dorsal fin and proposed a dynamic model of the interaction between the seahorse’s dorsal fin and seawater based on the hydrodynamic properties of seawater and the theory of fluid-structure coupling. A simulation model was established using the Fluent software, and the 3D fluid dynamic mesh was used to study the undulatory motion mechanism of the seahorse’s dorsal fin. The effect of the swing frequency, amplitude, and wavelength of the seahorse’s dorsal fin on its propulsion performance was studied. On this basis, an optimized design method was used to design a bionic seahorse’s dorsal fin undulatory motion mechanism. The paper has important guiding significance for the research and miniaturization of new underwater vehicles.